Adherence to the Standard Guidelines for Prescription of Antidiabetic Agents in Patients with Type 2 DM - Qasim M. Alhadidi, Ahmed S. Sahib, Ali M. Jaffer, Maha H. Ismael, Ekhlas K. Hassan, Saja M. Shareef, Asmaa M. Shoesh, Asia S. Dawood (Journal of Applied Pharmaceutical Science)
Prescription of appropriate antihyperglycemic agent depending on the standard guidelines has an important role in controlling diabetes and improving patient health. The aim of the present prospective study is to follow-up the adherence of prescribers to the standard guidelines for the prescription of anti-diabetic drugs in patients with type 2 diabetes mellitus. A prospective clinical trial was carried out on 64 individuals (43 patients and 21 healthy volunteers) of both sexes with the age range from 40-70 years. Parameters followed-up were fasting blood glucose (FBG), lipid profile, liver and renal function tests. The values of these parameters (at admission and after 3 months of follow-up) were calculated and compared with that of the control group and with the recommended treatment goals stated by American Diabetes Association (ADA) and the American Association of Clinical Endocrinologists (AACE/ ACE). Despite of continued treatment, no improvements were seen regarding followed-up parameters. It has been suggested that the adherence of prescribers to the standard guidelines for prescription of anti-diabetic agents is poor in our center, all patients evaluated have highly uncontrolled hyperglycemia where different anti-hyperglycemic drugs fail to attain glycemic control, and therapeutic strategy followed should be reconsidered.
Keywords: Type 2 DM, Diabetes guidelines, Hyperglycemia, oral hypoglycemic agents.